Potential effect of luteolin, epiafzelechin, and albigenin on rats under cadmium-induced inflammatory insult: In silico and in vivo approach - Shahzadi, Andleeb; Tariq, Nusrat; Sonmez, Haktan; Waquar, Sulayman; Zahid, Ayesha; Javed, Muhammad Ahsan; Ashraf, Muhammad Yasin; Malik, Arif; Ozturk, Munir (Frontiers in Chemistry, 2023)
Purpose High exposure to cadmium is a risk factor for many pathophysiological events. Induction of cyclooxygenase (COX)-2 is linked to inflammatory processes. Methods We, herein, performed in-silico experiments to check the binding affinity of phytochemicals and their therapeutic effect against COX-2 in cadmium administered rats. Wistar albino rats were given phytochemicals in different combinations to check their anti-inflammatory activities against cadmium intoxication. The level of ALT, 4HNE, 8-OHdG, TNF-α, IsoP-2α, COX-2 and MDA were estimated with their respective ELISA and spectrophotometric methods. Results The generated results show that phytocompounds possessed good binding energy potential against COX-2 and common interactive behaviour was observed in all docking studies. Moreover, the level of ALT, 4HNE, 8-OHdG, TNF-α, IsoP-2α, MDA and COX-2 were significantly increased in rats with induced toxicity as compared to the control group. Whereas, in combinational therapy of phytocompounds the levels were significantly decreased in the group. Conclusion Taken together, Luteolin, Epiafzelechin, and Albigenin can be used as anti-inflammatory therapeutic agents for future novel drug designing and thus, it may have therapeutic importance against cadmium toxicity.